2016
DOI: 10.1021/acs.jproteome.6b00530
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Investigation of Ram Spermatozoa and the Proteins Conferred by Seminal Plasma

Abstract: Sperm proteomes have emerged for several species; however, the extent of species similarity is unknown. Sheep are an important agricultural species for which a comprehensive sperm proteome has not been produced. In addition, potential proteomic factors from seminal plasma that may contribute to improved fertility after cervical insemination are yet to be explored. Here we use liquid chromatography-tandem mass spectrometry to investigate the proteome of ejaculated ram spermatozoa, with quantitative comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 111 publications
(180 reference statements)
1
35
0
Order By: Relevance
“…Focusing on the identified proteins, the first noticeable result was that all of them were present in all spermatozoa, independently of the source considered. Pini et al (24) reported similar results in ovine spermatozoa where only 0.5% of the proteins identified in epididymal spermatozoa were absent in ejaculated spermatozoa. These findings were somewhat expected knowing that mature spermatozoa have a very limited capacity to generate new proteins (2,26).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Focusing on the identified proteins, the first noticeable result was that all of them were present in all spermatozoa, independently of the source considered. Pini et al (24) reported similar results in ovine spermatozoa where only 0.5% of the proteins identified in epididymal spermatozoa were absent in ejaculated spermatozoa. These findings were somewhat expected knowing that mature spermatozoa have a very limited capacity to generate new proteins (2,26).…”
Section: Resultsmentioning
confidence: 62%
“…3C), the 21 hits found were mainly attributed to the extracellular region (8, 38%) and cell parts (7, 34%). DISCUSSION Sperm proteomes have been reported for mouse (19), human (20), monkey (21), equine (22) and most relevant livestock species including pig (15,23,24). However, to improve the understanding of complex regulate mechanisms involved in sperm function or to identify molecular causes of male infertility, the sperm proteome should be updated as the annotation of the protein-coding genome of each species has increased over time (3), as has recently been the case for pigs (16).…”
Section: Resultsmentioning
confidence: 99%
“…Human, bovine and ovine sperm as well as sperm from other animals share similar structural characteristics and a large number of proteins are conserved across sperm in these species human and bovine sperm (Skerget et al 2013, Holland & Ohlendieck 2015, Defaus et al 2016, Pini et al 2016. Similar Siglecs were often expressed in the same sperm regions in the different species and these patterns of expression suggest the presence of Siglec paralogues with potentially similar roles across species.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of sperm with a different surrounding medium seems to be the reason for such differences, resulting in changes in the lipid-protein composition of the plasma membrane, which in turn alters membrane stability and, ultimately, the sperm's ability to withstand cryopreservation [113,114]. A comparative proteomics analysis in fresh ram sperm revealed that three proteins (EDIL3, BSP5 and LEG1) from seminal plasma were only present in ejaculated sperm but not in epididymal sperm, whereas four membrane proteins (SPADH2, PPP1R7, BDH2 and RNASE9) were more abundant in ejaculated than epididymal sperm due to their higher concentration in the seminal plasma [115]. However, the role of these proteins in the reproductive and cryopreservation process still needs to be further characterized.…”
Section: Protein Namementioning
confidence: 99%